2013
DOI: 10.1111/irv.12082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of H1N1 on socially disadvantaged populations: summary of a systematic review

Abstract: BackgroundPrevious reviews found that the H1N1 pandemic was associated with a large proportion of hospitalizations, severe illness, workplace absenteeism, and high costs. However, the burden among socially disadvantaged groups of the population is unclear. This is a summary of a previously published systematic review commissioned by the World Health Organization on the burden of H1N1 pandemic (influenza A/Mexico/2009 (H1N1)) among socially disadvantaged populations.Methods MEDLINE and EMBASE were searched to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(219 reference statements)
0
8
0
Order By: Relevance
“…A large burden of 2009 H1N1 influenza was borne by lowincome countries. 14,15 India reported 39,977 cases and 2,113 deaths from H1N1 influenza between May 2009 and August 2010. 16 These numbers, which refer to laboratory-confirmed cases, are likely underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…A large burden of 2009 H1N1 influenza was borne by lowincome countries. 14,15 India reported 39,977 cases and 2,113 deaths from H1N1 influenza between May 2009 and August 2010. 16 These numbers, which refer to laboratory-confirmed cases, are likely underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Pandemic H1N1‐related hospitalization was significantly higher among American Indians, Blacks and Hispanics than among non‐Hispanic Whites in New Mexico, US, and was higher among persons of younger age and lower household income (Thompson et al, 2011 ). Similarly, Tricco, Lillie, Soobiah, Perrier, & Straus ( 2013 ) found significantly more hospitalizations among ethnic minorities versus nonethnic minorities in North America, yet no differences in ICU admissions or deaths among hospitalized patients in North America and Australia. They argued that their results suggest a similar burden of H1N1 between ethnic minorities and nonethnic minorities living in high‐income countries (Tricco et al, 2013 ).…”
Section: Evidence Of Morbidity and Mortality Disparitiesmentioning
confidence: 95%
“…Zhoe et al (2015) recommended the importance of quick screening for high-risk individuals for severe influenza, as they mentioned that highest risk group for mortality during the 2009/2010 influenza pandemic were those of Pakistani ethnicity followed by non-White ethnicity in comparison with White populations [11]. In addition, systematic review by Tricco et al showed that hospitalizations were significantly higher among ethnic minorities in comparison with nonethnic minorities during the influenza pandemic [12]. Therefore, it is plausible to suggest that if actions were taken at the time of influenza pandemic in 2009/2010, these actions in part may have decreased the highest mortality and mortality in BAME population during the COVID-19 pandemic in 2020.…”
Section: Introductionmentioning
confidence: 99%